2016
DOI: 10.1039/c5tb01877c
|View full text |Cite
|
Sign up to set email alerts
|

Novel triphosphorylation polyurethane nanoparticles for blood-contacting biomaterials' coating

Abstract: Novel polyurethane/sodium triphosphate nanoparticles were synthesized to enhance the blood compatibility of blood-contacting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It showed that the peaks for phosphorus at 2.0 keV and for silver at 3.0 keV. 44,45 This also indicated that Ag–STPP NPs were sucessfully introduced onto the surface of the PU film.…”
Section: Resultsmentioning
confidence: 92%
“…It showed that the peaks for phosphorus at 2.0 keV and for silver at 3.0 keV. 44,45 This also indicated that Ag–STPP NPs were sucessfully introduced onto the surface of the PU film.…”
Section: Resultsmentioning
confidence: 92%